Optical Properties of Rutile Single Crystals Grown Under Pressure by Tilting-Mirror-Type Floating Zone Method (Journal of Scientific Research, 2015)
Rutile single crystals with high quality and high transparency were grown successfully by tilting-mirror-type floating zone (TMFZ) technique. The grown crystals were characterized by polarized optical microscopy, X-ray diffractometer, UV-visible spectrophotometer and etch pits density measurement. The effect of applied pressure during growth on the optical properties and defect density of the rutile crystals were investigated. It was found that the rutile crystals grown under the high oxygen pressure are bright and transparent due to the lower concentration of defects, but rutile crystals grown at ambient or lower oxygen pressure exhibit deep blue color due to presence of defects such as dislocations and grain boundaries. The crystals grown under high oxygen pressure contains no low-angle grain boundaries, indicating that it can be used for high efficiency optical devices.